Efectiveness of Health Education using Flipchart Media on Health Cadres Knowledge About Climacterium in Susukan Village, Banjarnegara - Eti Yuliana; Kris Linggardini (Proceedings Series on Health & Medical Sciences, 2024)
Background: The climacterium is a transitional phase from the reproductive to the senium. During this period, women will experience several physical and psychological symptoms, so they need adequate knowledge. Forms of health services to the community can be conducted through the education of cadres through health education with various methods, one of which is by using flipchart media. Method: This research is a quantitative research with one group pretest and posttest. The sample was 32 health cadres in Susukan Village. The instrument is the pretest posttest questionnaire. Results: The results of the analysis obtained a Z value of -4.967 and a p value of 0.000, which means there is a difference in the knowledge of health cadres about the climacteric. A N-Gain Score of 76.67 means that health education using flipchart media is effective for the knowledge of health cadres about the climacteric. Conclusion: Health education using flipchart media is effective for health cadres knowledge about the climacterium in Susukan Village, Banjarnegara.